Analysis of Promotional Strategies to Increase Sales in The Creative Economy Business "Fatih Hydroponik" - Saputra, Rully Rezki; Yuliani, Helda; Rif'at, Rif'at (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the promotional strategies implemented by Fatih Hidroponik to increase sales of hydroponic vegetable products in an increasingly competitive market. Fatih Hidroponik, a modern agriculture-based creative economy business in Banjarmasin City and Barito Kuala Regency, relies on hydroponic cultivation methods to produce fresh, pesticide-free, and environmentally friendly vegetables. However, despite its superior quality, the main challenge is marketing it to gain wider public awareness. This study used a qualitative descriptive approach, collecting data through consumer interviews and observing Fatih Hidroponik's promotional practices. The results indicate that the promotional strategy prioritizes digital promotion through social media (Instagram and WhatsApp) and direct customer engagement. Although effective in increasing product awareness, some consumers suggested increasing the variety of promotional content. Recommendations made in this study include optimizing the use of paid advertising on social media, increasing the variety of promotional content, and collaborating with local influencers to increase product exposure. This research is expected to provide insights and guidance for Fatih Hidroponik and similar businesses in designing more effective promotional strategies to increase sales and competitiveness in the market.